2016
DOI: 10.17576/3l-2016-2201-08
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming Voices and Disputing Authority: A Feminist Dialogics Approach in Reading Kee Thuan Chye’s Plays

Abstract: Kee Thuan Chye in all four of his selected plays has appropriated and reimagined history by giving it a flair of contemporaneity in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Literary studies have dwelled mostly on the thematic aspects of Kee's plays, for instance, from existentialist, feminist and political perspectives (Bakar et al, 2016;Rajoo, 2001;Tneh, 2016). The infusion of wayang kulit has also been discussed closely with the subject matters of the plays which often manifest a clash between cultural identity and the dominant culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literary studies have dwelled mostly on the thematic aspects of Kee's plays, for instance, from existentialist, feminist and political perspectives (Bakar et al, 2016;Rajoo, 2001;Tneh, 2016). The infusion of wayang kulit has also been discussed closely with the subject matters of the plays which often manifest a clash between cultural identity and the dominant culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Her statement implies a feminist aspect that defends women's rights in order to be equal to men. Hence, based on the previous researches and theories conducted by Jespersen (1922), Lakoff (2009), Nienaber and Moraka (2016), Bakar, Yusof, and Vengadasamy (2016), which have examined feminism and feminist language. It is proved that the researches' impacts have been continuing until today.…”
Section: Figure 3 the Poster Of Yogyakarta's Students'mentioning
confidence: 99%
“…Meanwhile, Nienaber and Moraka (2016) have stated that feminism concerns the identity of women, both philosophically and socially, and with equal rights politically, legally, and economically. In addition, another research by Bakar, Yusof, and Vengadasamy (2016), has revealed that feminism is an effort that aims to reclaim the voice and history of previously muted women by allowing them to express their voices and acknowledging them for their opinions since the separation between men and women is challenging in the general discourses (Udasmoro, 2017). It is in line with Shamsuddin and Hamid (2017), who have stated that there should be a long study of gender roles that conform to social and cultural expectations.…”
Section: Introductionmentioning
confidence: 99%